(untitled) (Mugda Medical College Journal, 2026)
A cross-sectional, comparative study was conducted in the Department of Radiology & Imaging, Shaheed Suhrawardy Medical College Hospital, Dhaka, Bangladesh, between July and December of 2019, to assess the diagnostic usefulness of multi-detector computed tomography scans in the evaluation of neck mass by comparing with histopathological reports. A total of 40 patients were enrolled in the study. All relevant data was collected from history sheet of the patients and investigation reports. Computed Tomography findings and histopathological diagnosis were recorded in a pre-designed structured data collection sheet. Then histopathology reports were compared with computed tomography (CT) scan findings. The most common age group was 40-70 years (45%), followed by 15-40 years (35%) and <15 years (12.5%). A male predominance was observed with male-female ratio of 2.33:1. Based on CT scans, 14 patients were diagnosed as benign lesions such as thyroglossal duct cyst 1case, abscess 2 cases, tubercular lymphadenopathy 2 cases, reactive lymphadenopathy 1 case, multinodular goiter 3 cases, thyroid cyst 1 case, hemangioma 1 case, pleomorphic adenoma 2 cases and carotid body tumor 1 case. The rest 26 cases were diagnosed as malignant: carcinoma larynx 5 cases, metastatic lymphadenopathy 3 cases, carcinoma thyroid 2 cases, parotid carcinoma 3 cases, submandibular gland malignant tumor 1 case, carcinoma tonsil 2 cases, nasopharyngeal carcinoma 4 cases, hypopharyngeal carcinoma 1 case, carcinoma base of tongue 2 cases and lymphoma 3 cases. Based on histopathology reports, 13 patients were diagnosed as having benign pathology like thyroglossal duct cyst 1case, abscess 3 cases, tubercular lymphadenopathy 2 cases, reactive lymphadenopathy 1 case, multinodular goiter 2 cases, thyroid cyst 1 case, pleomorphic adenoma 2 cases and carotid body tumor 1 cases. Remaining 27 cases were diagnosed as malignant which included carcinoma larynx 5 cases, metastatic lymphadenopathy 4 cases, carcinoma thyroid 2 cases, parotid carcinoma 3 cases, submandibular gland malignant tumor 1 case, carcinoma tonsil 2 cases, nasopharyngeal carcinoma 4 cases, hypopharyngeal carcinoma 1 case, carcinoma base of the tongue 2 cases and lymphoma 3 cases The present study showed that CT scans were significantly precise to differentiate between benign and malignant neck masses with 92.6% sensitivity, 92.3% specificity and 92.5% diagnostic accuracy. Our study demonstrated that computed tomography scan proved to be a useful tool for assessing and characterization of neck mass as either benign or malignant. Mugda Med Coll J. 2026; 9(1): 25-30